Quizizz Application-Based Interactive Learning Media Development Workshop for Junior High School Teacher - Faiza Fadiyah; Anis Fuadi; Nurjannah Nurjannah; Irmayanti Irmayanti; Wang Lita (Yayasan Adra Karima Hubbi, 2023)
Background. The thing that makes learning boring is learning that is monotonous and does not use learning media. This digital era requires teachers to use digital-based and interactive media. One application that can be used in learning is quizizz. This application resembles learning that is packaged in the form of games so that students are very happy to participate in learning. Purpose. This activity aims to develop interactive learning media based on the Quizizz application for junior high school teachers in Sinjai besides teachers and students can implement fun and enjoyable learning. Method. The method used in this activity is the Workshop. This activity was carried out at the UPTD SMPN 6 Sinjai where at this school teachers were still minimal in using computer-assisted learning media. The learning media developed is application-based media (Quiziz application). The stages of implementing activities are planning, implementation and evaluation. This planning was carried out by observing at SMPN 6 Sinjai and socializing with the school principal and teachers. The implementation carried out is the delivery of materials and practices in developing Quizizz-based media. While the evaluation is the participants giving an assessment of this workshop activity. Results. The results achieved in this activity were that the workshop participant teachers had increased their understanding of learning media by using the Quizizz application and were able to apply it in learning. Conclusion. In conclusion, this quizizz application can make it easier for teachers to develop digital-based learning media and make learning more enjoyable for students.